Family structure and multisite musculoskeletal pain in adolescence: a Northern Finland Birth Cohort 1986 study - Eveliina Heikkala; Petteri Oura; Jaro Karppinen; Annie Herbert; Heidi Varis; Maria Hagnäs; Ilona Mikkola; Markus Paananen (BMC Musculoskeletal Disorders, 2023)
Abstract Background Family structure is suggested to be associated with adolescent pain, but evidence on its association with multisite MS pain is sparse. The purpose of this cross-sectional study was to investigate the potential associations between family structure (‘single-parent family’, ‘reconstructed family’, and ‘two-parent family’) and multisite musculoskeletal (MS) pain in adolescence. Methods The dataset was based on the 16-year-old Northern Finland Birth Cohort 1986 adolescents with available data on family structure, multisite MS pain, and a potential confounder (n = 5,878). The associations between family structure and multisite MS pain were analyzed with binomial logistic regression and modelled as unadjusted, as the evaluated potential confounder, mother’s educational level, did not meet the criteria for a confounder. Results Overall, 13% of the adolescents had a ‘single-parent family’ and 8% a ‘reconstructed family’. Adolescents living in a single-parent family had 36% higher odds of multisite MS pain compared to adolescents from two-parent families (the reference) (Odds Ratio [OR]: 1.36, 95% Confidence Interval [CI]: 1.17 to 1.59). Belonging to a ‘reconstructed family’ was associated with 39% higher odds of multisite MS pain (OR 1.39, 1.14 to 1.69). Conclusion Family structure may have a role in adolescent multisite MS pain. Future research is needed on causality between family structure and multisite MS pain, to establish if there is a need for targeted support.